2007
DOI: 10.1210/me.2006-0503
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc Finger Protein Ras-Responsive Element Binding Protein-1 Is a Coregulator of the Androgen Receptor: Implications for the Role of the Ras Pathway in Enhancing Androgenic Signaling in Prostate Cancer

Abstract: Androgen receptor (AR) plays an important role in normal prostate function as well as in the etiology of prostate cancer. Activation of AR is dictated by hormone binding and by interactions with coregulators. Several of these coregulators are known targets of Ras-related signals. Recent evidence suggests that Ras activation may play a causal role in the progression of prostate cancer toward a more malignant and hormone-insensitive phenotype. In the present study, we used a transcription factor-transcription fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
51
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…Despite its implication in Ras, Ral, p16, p53, and androgen receptor 10,11,14,19,20 signaling pathways, sparse data exist regarding the nature, expression, or function of RREB1 mRNA and protein in cancer cells. This is the first study to address this gap by describing RREB1 expression in human cancers, as well as the first to examine isoform expression in human tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite its implication in Ras, Ral, p16, p53, and androgen receptor 10,11,14,19,20 signaling pathways, sparse data exist regarding the nature, expression, or function of RREB1 mRNA and protein in cancer cells. This is the first study to address this gap by describing RREB1 expression in human cancers, as well as the first to examine isoform expression in human tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Mukhopadhyay et al 20 reported that RREB1 binds AR and inhibits its function as a transcription factor. In addition, RREB1 binding and inhibition of AR activity was relieved by activated Ras signaling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations